Detection of the Chandler Wobble of Mars From Orbiting Spacecraft. Issue 21 (3rd November 2020) - Konopliv, Alex S.; Park, Ryan S.; Rivoldini, Attilio; Baland, Rose‐Marie; Le Maistre, Sebastien; Van Hoolst, Tim; Yseboodt, Marie; Dehant, Veronique
Abstract: For the first time for any planetary body other than the Earth, the free wobble of the pole called the Chandler wobble has been detected for Mars with a period of 206.9 ± 0.5 days and amplitude of 10 cm from radio tracking observations of Mars Odyssey, Mars Reconnaissance Orbiter (MRO), and Mars Global Surveyor (MGS), in order of decreasing sensitivity. The motion of the rotation pole location on the surface of Mars, or polar motion, is observed using two different approaches: (1) joint global estimates of Mars' orientation and its gravity field and (2) time series solutions of C 21 and S 21 . For Mars interior models, the Chandler wobble period is combined with other measurements including the moments of inertia from our estimated precession rate ψ ̇ = − 7603.9 ± 1.3 mas / year and tidal Love number k 2 = 0.169 ± 0.006. The Chandler wobble period constrains the rheology of the Martian mantle and in particular its long‐term frequency dependence. Plain Language Summary: For the first time for any solar system body other than the Earth, one component of the motion of the Mars spin axis on the surface of Mars, called the Chandler wobble, has been detected. The motion has a period of 206.9 ± 0.5 days, an amplitude of 10 cm on the surface, and is in a nearly circular counterclockwise direction as viewed from the North Pole. The pole motion is determined from radio tracking observations of Mars Odyssey, Mars Reconnaissance Orbiter, and Mars Global Surveyor, in order of decreasing sensitivity. The detection of the Chandler wobble improves our understanding of energy dissipation in the mantle for time intervals near the wobble period. Key Points: For the first time, the Chandler wobble has been detected for a solar system body other than the Earth The Chandler wobble is visible in the tracking data from two Mars orbiting spacecraft The Chandler wobble significantly improves our understanding of the long period behavior of the mantle rheology